Trait paranoia shapes inter-subject synchrony in brain activity during an ambiguous social narrative - Emily S. Finn (Nature Portfolio, 2018)
Reactions to the same event can vary vastly based on multiple factors. Here the authors show that people with high trait-level paranoia process ambiguous information in a narrative differently and this can be attributed to greater activity in mentalizing brain regions during the moments of ambiguity.